The Phosphatidylinositol 3-Kinase/mTor Pathway as a Therapeutic Target for Brain Aging and Neurodegeneration - David Heras-Sandoval; Evangelina Avila-Muñoz; Clorinda Arias (MDPI AG, 2011)
Many pathological conditions are associated with phosphatidylinositol 3-kinase (PI3K) dysfunction, providing an incentive for the study of the effects of PI3K modulation in different aspects of diabetes, cancer, and aging. The PI3K/AKT/mTOR pathway is a key transducer of brain metabolic and mitogenic signals involved in neuronal proliferation, differentiation, and survival. In several models of neurodegenerative diseases associated with aging, the PI3K/AKT pathway has been found to be dysregulated, suggesting that two or more initiating events may trigger disease formation in an age-related manner. The search for chemical compounds able to modulate the activity of the PI3K/AKT/mTOR pathway is emerging as a potential therapeutic strategy for the treatment and/or prevention of some metabolic defects associated with brain aging. In the current review, we summarize some of the critical actions of PI3K in brain function as well as the evidence of its involvement in aging and Alzheimer's disease.